3G post adoption users experience with telecommunications services: A partial least squares (PLS) path modelling approach. Issue 3 (1st August 2016) - Rezaei, Sajad; Amin, Muslim; Moghaddam, Minoo; Mohamed, Norshidah
Abstract : Purpose: The purpose of this study is to examine the impact of service quality, perceived usefulness and users' cognitive satisfaction to determine the third-generation (3G) mobile phone users' behavioural retention in using 3G telecommunications services. Design/methodology/approach: A total of 243 valid questionnaires were collected from 3G users in the Klang Valley, Malaysia. The combination of partial least squares (PLS) path modelling approach and structural equation modelling (SEM; PLS-SEM) technique was used to analyze the measurement and structural model. Findings: Our empirical assessment supports the proposed research hypotheses and further suggests that service quality is a second-order reflective construct comprising navigation and visual design, management and customer service and system reliability and connection quality. Originality/value: Prior studies have examined the impact of service quality, perceived usefulness, overall users' satisfaction and behavioural intention on an information system in general. This study is among the few studies that have attempted to gain insights into 3G users' post-adoption experience with telecommunications services.